Atomistic structure of alkali-silica reaction products refined from X-ray diffraction and micro X-ray absorption data. (March 2020) - Geng, Guoqing; Shi, Zhenguo; Leemann, Andreas; Borca, Camelia; Huthwelker, Thomas; Glazyrin, Konstantin; Pekov, Igor V.; Churakov, Sergey; Lothenbach, Barbara; Dähn, Rainer; Wieland, Erich
Abstract: The alkali-silica reaction (ASR) causes internal expansion that leads to severe concrete degradation. The structure of the ASR products remains largely unclear, due to the limitation of laboratory probes in micro-chemical-crystallographic study. We hereby performed synchrotron-radiation-based X-ray absorption spectroscopy and diffraction investigations to both ASR product samples collected from the field, and reference samples with known structure. Our results suggest that the field ASR crystals from distinct sources are nearly identical. They share a layer-silicate structure similar to the mineral shlykovite, whereas the stacking of the layers in field ASR crystals is altered in several ways, such as the variable basal spacing and significant glide of adjacent layers along the b -axis. We also demonstrate that the amorphous ASR product highly resembles C-S-H. Our study adds new insights to the atomistic structure of ASR products.